Pendekatan STEAM-PjBL untuk Mengembangkan Scientific Creativity Siswa Kelas V Pada Topik Ekosistem dan Magnet - Yulia, Dinda Candra; Rahmawati, Yuli; Darwis, Darsef (Cetta: Jurnal Ilmu Pendidikan, 2024)
This research aims to develop students' scientific creativity through the STEAM-PjBL approach. The issues identified during observation were that students were less active during lessons, not enthusiastic about attending classes, and did not pay attention to the teacher's explanations. This was due to the monotonous and less varied teaching methods used by the teacher. The STEAM-PjBL approach was chosen because of its significant impact on developing students' scientific creativity and fostering group collaboration in the context of science learning by relating it to everyday life. This study employs classroom action research with three cycles and two different projects. Data were collected through interviews, observations, reflective journals, researcher notes, and students' scientific creativity results. Unusual use, real advance, technical production, science imagination, science problem solving, creative experimental, and science product are aspects of scientific creativity. This research involved 30 fifth-grade elementary school students. Students worked in groups to create projects related to ecosystem and magnet topics. The results showed that the STEAM-PjBL approach on ecosystem and magnet topics developed scientific creativity. In cycle III, there was a significant improvement in the aspects of unusual use and science imagination, with an increase of 16.25% from the initial scores of 15.83% and 15.42%, respectively. The results of observations on learning activities using the STEAM-PjBL approach can stimulate and develop students' scientific creativity in a scientific context.